2012
DOI: 10.1016/j.jhealeco.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and health: Lessons from a refugee residential assignment program

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 50 publications
(57 reference statements)
1
36
0
1
Order By: Relevance
“…Instead, we followed prior research in which the sample was identified based on the year and region of migration to Sweden. 2, 14 Government statistics show that most immigrants to Sweden during the study period were refugees (46.5%) or those moving to rejoin family members (i.e., “tied movers”) (47.7%), compared to labor immigrants (0.6%), guest students (2.4%), or adopted children (2.7%). Adopted children and many students would not meet our age inclusion criterion, and we exclude tied movers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Instead, we followed prior research in which the sample was identified based on the year and region of migration to Sweden. 2, 14 Government statistics show that most immigrants to Sweden during the study period were refugees (46.5%) or those moving to rejoin family members (i.e., “tied movers”) (47.7%), compared to labor immigrants (0.6%), guest students (2.4%), or adopted children (2.7%). Adopted children and many students would not meet our age inclusion criterion, and we exclude tied movers.…”
Section: Discussionmentioning
confidence: 98%
“…In our search of the broader literature on neighborhood health effects, we found no other randomized trials and one quasi-experimental study, which found no relationship between neighborhood-level income inequality and hospitalization risk. 2 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have exploited the quasi-experimental feature of dispersal policies to assess health outcomes. One of these has assessed the association between neighbourhood income inequality (based on the Gini coefficient) and the risk of being admitted to hospitals among refugees in Sweden and found no statistically significant effect of the exposure on the outcome 25. Another study from Sweden created a historical cohort to test the hypothesis that neighbourhood deprivation affects the development of type 2 diabetes among refugees quasi-randomly assigned to neighbourhoods throughout the country 26.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable body of research demonstrates the impact of societal-level distribution of income on health, and mortality (Marmot and Wilkinson 1999;Raphael 2004;Auger and Raynault 2006;Gronqvist et al 2012). People who live in areas with higher income inequality have poorer health and higher mortality rates (Gronqvist et al 2012).…”
Section: Economic Environmentmentioning
confidence: 99%